2020
DOI: 10.1038/s41591-020-1070-6
|View full text |Cite
|
Sign up to set email alerts
|

Ad26 vaccine protects against SARS-CoV-2 severe clinical disease in hamsters

Abstract: Coronavirus disease 2019 (COVID-19) in humans is often a clinically mild illness, but some individuals develop severe pneumonia, respiratory failure and death1–4. Studies of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in hamsters5–7 and nonhuman primates8–10 have generally reported mild clinical disease, and preclinical SARS-CoV-2 vaccine studies have demonstrated reduction of viral replication in the upper and lower respiratory tracts in nonhuman primates11–13. Here we show that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
381
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 293 publications
(444 citation statements)
references
References 26 publications
53
381
0
4
Order By: Relevance
“…However, sVNT and pVNT reported in this study have well demonstrated a significant correlation with cVNT in NAb titers to SARS-CoV-2 ( P <0.0001, R =0.7678-0.8591) ( 28 ). This was also evidenced by close correlation between ELISA and pVNT or cVNT by other studies using adenovirus vectored COVID-19 vaccines in rhesus macaques ( P <0.0001, R =0.8314-0.8427) ( 12 ), hamsters ( P <0.0001; R =0.7849) ( 13 ) and human clinical phase II trial ( P <0.0001, R =0.72-0.75) ( 9 ). In addition, compared with a panel of convalescent serum samples from COVID-19 patients the level of binding or neutralizing antibodies observed in this study was favorable and in line with all other published data from COVID-19 vaccines.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, sVNT and pVNT reported in this study have well demonstrated a significant correlation with cVNT in NAb titers to SARS-CoV-2 ( P <0.0001, R =0.7678-0.8591) ( 28 ). This was also evidenced by close correlation between ELISA and pVNT or cVNT by other studies using adenovirus vectored COVID-19 vaccines in rhesus macaques ( P <0.0001, R =0.8314-0.8427) ( 12 ), hamsters ( P <0.0001; R =0.7849) ( 13 ) and human clinical phase II trial ( P <0.0001, R =0.72-0.75) ( 9 ). In addition, compared with a panel of convalescent serum samples from COVID-19 patients the level of binding or neutralizing antibodies observed in this study was favorable and in line with all other published data from COVID-19 vaccines.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we generated two novel adenovirus vectored COVID-19 vaccines encoding the full-length S gene of SARS-CoV-2. The intact S glycoprotein rather than the shorter S or RBD proteins was shown to be the most effective antigen eliciting protective immunity against SARS-CoV-2 infection in DNA vaccines and Ad26 vectored vaccines ( 12,13,26 ). The vectors Sad23L and Ad49L originated from simian adenovirus type 23 and human adenovirus type 49, respectively ( 22, 23 ), are novel adenoviral vector.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted September 25, 2020. ; https://doi.org/10.1101/2020.09.23.20199604 doi: medRxiv preprint 99% seroconversion in each dose group (Figure 2A). Of the cohort 1a participants who were seropositive at baseline, 7 out of 8 and 2 out of 3 demonstrated the preset criterion of a 4-fold 227 increase in binding antibody titer to be considered a vaccine responder, for the 5x10 10 and 1x10 11 vp dose level groups, respectively. The initial 15 enrolled participants in cohort 3 were seronegative at baseline and had seroconverted by Day 29 post vaccination with GMTs of 507 (95% CI: 181; 1418) and 248 (95% CI: 122; 506), for the 5x10 10 and 1x10 11 vp dose level group, 231…”
Section: Immunogenicity Of Ad26cov2s 220mentioning
confidence: 99%
“…We randomly assigned 405 eligible participants 18-55 years of age and 405 participants >65 years of age to receive one or two vaccinations with either a 5x10 10 or 1x10 11 vp dose level of vaccine, or placebo (1:1:1:1:1 per age group): 5x10 10 vp/5x10 10 vp; 5x10 10 vp/placebo; 1x10 11 vp /1x10 11 vp; 1x10 11 vp/placebo; or placebo/placebo for the first and second dose, respectively (Figure 1).…”
Section: Randomization and Blindingmentioning
confidence: 99%
See 1 more Smart Citation